Efficient isolation of rare B cells using next-generation antigen barcoding - Hurtado, Jonathan; Flynn, Claudia; Lee, Jeong Hyun; Salcedo, Eugenia C.; Cottrell, Christopher A.; Skog, Patrick D.; Burton, Dennis R.; Nemazee, David; Schief, William R.; Landais, Elise; Sok, Devin; Briney, Bryan (Frontiers in Cellular and Infection Microbiology, 2023)
The ability to efficiently isolate antigen-specific B cells in high throughput will greatly accelerate the discovery of therapeutic monoclonal antibodies (mAbs) and catalyze rational vaccine development. Traditional mAb discovery is a costly and labor-intensive process, although recent advances in single-cell genomics using emulsion microfluidics allow simultaneous processing of thousands of individual cells. Here we present a streamlined method for isolation and analysis of large numbers of antigen-specific B cells, including next generation antigen barcoding and an integrated computational framework for B cell multi-omics. We demonstrate the power of this approach by recovering thousands of antigen-specific mAbs, including the efficient isolation of extremely rare precursors of VRC01-class and IOMA-class broadly neutralizing HIV mAbs.